A new and likely extinct species of Antilissus Sharp, 1879 (Coleoptera: Zopheridae: Colydiinae) from Makauwahi Cave, Kauai, Hawaiian Islands - Porch, Nick (Zootaxa, 2020)
This paper describes Antilissus makauwahi, sp. nov., from the subfossil record of Makauwahi Cave on the island of Kauai, Hawaii. This new species is the second species of Antilissus Sharp from Hawaii and second described species for the genus. The type species of Antilissus, A. aper Sharp, has been widely collected from under the bark of dead or dying trees, at higher elevations, on all major Hawaiian Islands. In contrast, A. makauwahi is so far known only from a small number of subfossil sclerites recovered from sediments dating to before human arrival in Hawaii (>800 years before present). This potentially extinct species adds to the growing body of evidence suggesting the widespread extinction of Pacific island insects after human arrival.